An in vitro model for assessment of excitotoxicity induced by glutamate and neuroprotection using digitized fluorescent imaging of mitochondrial potentials - Muhyaddin, Mohammed Sherwan (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objectives: The established methods to demonstrate the neuroprotective efficacy of drugs still use in vivo animal tests. The objective of the present study, therefore, was to develop in vitro screening systems based on digitized fluorescent imaging of individual neurons from neuronal cell cultures as a practical model for assessment of neuroprotectors during excitotoxicity. Methods: Cortical cells from embryonic mice were cultivated on glass coverslips Cells were loaded with the fluorescence dye rhodamine-123. The coverslips were mounted in a temperature controlled flow-through chamber. The superfusion chamber was mounted on an inverted microscope. The emission light after excitation of the dye was measured with an intensified CCD camera, accordingly the changes in the mitochondrial membrane potential were monitored. Results: Neurotoxic concentrations of glutamic acid induced a rapid and irreversible damage to mitochondrial membrane potential. The non-competitive NMDA-receptor antagonist MK-801 (dizocilpine) preserved neuronal viability. The loss of rhodamine-123 fluorescence highly correlated with the ongoing neuronal cell death and was shown to be a suitable parameter to determine the neuroprotective action of pharmaceutical compounds. Conclusion: Loss of the mitochondrial membrane potential can be used as dynamic markers of cellular injury in vitro. Presumably, the in vivo animal experiments are required and cannot be avoided completely. However, the described approach can at least enlighten the preliminary neuroprotective effect of drugs or their critical concentrations directly on the neuronal level and by that way avoid a large number of animal tests.